Dampak Penggunaan Gadget Terhadap Kemampuan Intraksi Sosial Anak Usia Dini - Diah Saputri, Adek; Ayuning Pambudi, Diah (ACIECE, 2018)
Gadget is one of the technologies that are currently popular, both among adults and childrenwho use it. There are so many gadget that are produced that many children are being targetedas a target, so that now children have become active consumers of users. Gedget has a hugeinfluence on human life, as well as on children. if the childhood is already addicted andnegatively affected by the gadget, the child's development will be hampered. this can lead tosocial interaction between children and the community, the environment will be reduce. as weknow, that early age is the age at which children can enjoy the ability to socialize well in thesurrounding environment. in this phase the child is also very very span with what he sees andwhat he hears. parents must be more careful in giving games, especially with media gadgets, sothat the child must be given supervision, time limits, and taught to play with their peers, so thatchildren can interact with the surrounding environment